PENGARUH PROMOSI TERHADAP PENGENALAN MAHASISWA PADA UNIVERSITAS ISLAM OKI (UNISKI) KAYUAGUNG - Fernandes, Ari (MOTIVASI, 2021)
Purpose This research was conducted at the Oki Islamic University, which is located at Jalan Lieutenant Muchtar Saleh, the former office of the Oki Regent. The formulation of the problem in this study is to determine how the effect of promotion on the introduction of students at the Oki Islamic University.Design / methodology The sampling method in this study is stratified random sampling, the data used in this study is primary data, namely data collected directly through the object. The data can be in the form of answers to questionnaires from Oki Islamic University students. As for secondary data, namely data that has been further processed in the form of a brief history of Uniski, The method of analysis in this study is qualitative and quantitativeFindings From the results of this study indicate that the promotion carried out by the Oki Islamic University through brochures, which stated very often and sometimes was 52.6% and those who answered only once and never answered 47.4%, through banners stating very often and sometimes it was 66.8%, and those who stated only once and never were 33.2%. Through social media, those who stated very often and sometimes were 41.3%, and those who stated once and never were 60.4%. Meanwhile, through radio, those who stated very often and sometimes were 39.6% and those who stated only once and never were 60.4%. Thus, brochures and banners have an impact on students' introduction to Islamic universities, while promotions through social media and radio have less impact. Therefore, the promotion carried out by Uniski through brochures, banners, needs to be improved because it has a more useful impact on the introduction of students to the Oki Islamic University.